The Globalization of Higher Education and the Future of European Universities - Sotirofski, Kseanela (Richtmann Publishing, 2010)
The thesis of this article is that the Lisbon Treaty is one of the main factors that push the European and European candidate countries universities to rethink about a common reorganization in the years to come. Higher education is doubly affected by the local post-1989 transformations and by more profound and more long-lasting global transformations. So, the Lisbon Treaty is considered as one of the key forces that will push the Albanian and European Higher Education institutions to be the key factor of implementation of the treaty requirements directly to the students that are the future of Europe changes. A brief summary of related literature review and some qualitative data collected from an in-depth interview with 45 university students of private and public universities will be analyzed. Among all traditional factors that determine the possible implementation fields of the Treaty the author finds that the factors like the teaching of democratic and transparency feelings and thoughts, common efficiency of European universities, the promoting of European rights and values, freedom, solidarity and security and the notification of European universities as an actor on the global stage are statistically important.